Design of a quencher for gases from pyrolysis of used tyres - Gyllén, Patrik (My University, 2014)
A quencher with recirculation was designed for cooling of hot gases from pyrolysis of used tyres. This thesis evaluates the heat transfer mechanisms and operational parameters affecting the design of this particular quencher. By deriving two different theoretical models describing the heat transfer between sprayed oil droplets and hot gases entering a quencher, and then applying the calculations in an existing quencher. Correlations between theory and experiments on the existing quencher where evaluated, the correlations functioned as a base for determining a new volume of the exsisiting quencher.
Keywords: Energiteknik; Energy Engineering